Answer:
4*x^4*y^22
Step-by-step explanation:
Your goal here is to REDUCE the given expression to simplest terms.
One way in which to approach this problem would be to rewrite (2x^2y^10)^3 as: (2x^2*y^8)*y^2*(2x^2*y^10)^2.
Dividing this rewritten expression by 2x^2*y^8 results in:
y^2(2x^2*y^10)^2.
We now need to raise (2x^2*y^10) to the power 2. Doing this, we get:
4x^4*y^20.
Multiply this by y^2 (see above):
y^2*4x^4*y^20
The first factor is 4: 4y^2*x^4*y^20. This is followed by the product of y^2 and y^20: 4*y^22*x^4
Finally, this should be re-written as
4*x^4*y^22
Another way of doing this problem would involve expanding the numerator fully and then cancelling out like factors:
8*x^6*y^30 4*x^4*y^22
----------------- = ------------------ = 4*x^4*y^22
2x^2y^8 1
Remember
we can do anything to an equation as long as we do it to both sides
try to isolate the variable
you have 2 types
x+b=c
x/b=c
fior the first type, minus b from both sides to get
x=c-b
for the second, multiply both sides by b to get rid of the fraction to get
x=cb
also remember that -x times -1=x
b.add 25 to both sides
-a=20
multiply -1
a=-20
c.
-t/8=-4
multiply both sides by 8
-t=-32
mutiply -1
t=32
d. -n/-5=-30
mulitply both sides by -5
-n=150
multiply both sides by -1
n=-150
e. multiply both sides by 12
-l=144
multiply b y-1
l=-144
Yes...the person's hypothesis could be correct.
540 (100 centimeters = 1 meter, so 54 x 100 = 540.)